Heterogeneity evaluation of multi-high b-value apparent diffusion coefficient on cerebral ischemia in MCAO rat - Shi, Liwei; Yu, Bo; Chen, Qiuyan; Zheng, Tianxiu; Xing, Peiqiu; Wei, Dingtai (Frontiers in Neuroscience, 2022)
Purpose: To assess brain damage in a rat model of cerebral ischemia based on apparent diffusion coefficient (ADC) data obtained from multi-high b-values and evaluate the relationship between Aquaporin 4(AQP4) expression and ADC. Methods: 38 male Sprague-Dawley rats were randomized into two groups:(1) sham controls(n=6) and (2) cerebral ischemia (successful model, n=19). All rats underwent diffusion-weighted imaging (DWI) with both standard b-values and multi-high b-values (2500–4500 s/mm2) using a 3.0-T device. Standard ADC(ADCst) maps and multi-high b-value ADCs (ADCmh) were calculated respectively. Aquaporin 4 expression was quantified using Western blot. Relative values of ADCst and ADCmh, AQP4 expression were compared between the sham group and the ischemia group. Correlations between ADC values and AQP4 expression were evaluated. Results: At 0.5h after suture insertion, the value of ADCmh on the lesion was obviously decreased, and there was no difference in lesion volume when compared with ADCst. After reperfusion, besides similar regions where ADCst values decreased, we also found additional large values on ADCmh within the cortex of the ipsilateral side or surrounding the lesion. The lesion evolution of the large value on ADCmh was quite different from other indicators. But the total ADCmh values were still significantly associated with ADCst. The AQP4 protein expression level was appreciably increased after MACO, but there was no correlation between AQP4 expression either with ADCmh or ADCst. Conclusion: We found the large values on ADCmh during the progression of cerebral infarction is varied, but there was no correlation between ADCmh values and AQP4 expression. ADCmh may indicate the heterogeneity of ischemia lesions, but the underlying pathological basis should be further explored.